PAG3 promotes the differentiation of bloodstream forms in Trypanosoma brucei and reveals the evolutionary relationship among the Trypanozoon trypanosomes - Wen, Yan-Zi; Tang, Hao-Tian; Cai, Xiao-Li; Wu, Na; Xu, Jia-Zhen; Su, Bi-Xiu; Hide, Geoff; Lun, Zhao-Rong; Lai, De-Hua (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Trypanosoma brucei, T. evansi and T. equiperdum are members of the subgenus Trypanozoon and are highly similar morphologically and genetically. The main differences between these three species are their differentiation patterns in the hosts and the role of vectors in their life cycles. However, the mechanisms causing these differences are still controversial. Methods PAG3 gene was accessed by PCR amplification in 26 strains of Trypanozoon and sequences were then analyzed by BLAST accompanied with T. evansitype B group. RNA interference and CRISPR/Cas9 were used for revealing possible role of PAG3 in slender to stumpy transformation. Results The procyclin associated gene 3 (PAG3) can be found in the pleomorphicspecies, T.brucei, which undergoes differentiation of slender forms to the stumpy form. This differentiation process is crucial for transmission to the tsetse fly vector. However, a homologue of PAG3 was not detected in either T. evansi or in the majority of T. equiperdum strains which are allmonomorphic. Furthere xperiments in T. brucei demonstrated that, when PAG3 was down-regulated or absent, there was a significant reduction in the differentiation from slender to stumpy forms. Conclusion Therefore, we conclude that PAG3 is a key nuclear gene involved in the slender to stumpy differentiation pathway of T.brucei in the mammalian host. Loss of this gene might also offer a simple evolutionary mechanism explaining why T. evansi and some T. equiperdum have lost the ability to differentiate and have been driven to adapt to transmission cycles that by pass the tsetse vector or mechanical contact.